Soil settled on velvetleaf Abutilon theophrasti affects optimal carrier volume for trifloxysulfuron - Akbar Aliverdi; Samira Karami (Journal of Crop Protection, 2021)
Whether a soil is settled on velvetleaf Abutilon theophrasti (Malvaceae) or not, it was not clear if the concentration of spray droplets could influence the effectiveness of trifloxysulfuron. In an experiment, 12 g ha–1 trifloxysulfuron was sprayed at 135 l ha–1 on velvetleaf treated with 0, 4, 8, 12, 16, and 20 kg soil ha–1 through two soil treatment methods, one within a soil dust chamber and the other with a simulated muddy rain. In another experiment, velvetleaf was treated with 20 kg soil ha–1 and exposed to the airflow of 0 and 10 km h–1. Then 12 g ha–1 trifloxysulfuron was sprayed at 135, 180, 225, 270, 360, and 450 l ha–1. The effectiveness of trifloxysulfuron was negatively correlated with the rate of soil settled on velvetleaf. When the source of soil was a simulated muddy rain, compared to the soil dust chamber, it had a more negative effect on the effectiveness of trifloxysulfuron. Besides, it was not removed from velvetleaf by the airflow before spraying. The effectiveness of trifloxysulfuron was correlated with carrier volume. Correlation type was affected by soil settled on velvetleaf. A positive correlation was observed in soil-treated velvetleaf, especially within the soil dust chamber. Therefore, larger, more diluted droplets were needed to obtain the best trifloxysulfuron efficacy. Unlike in non-treated velvetleaf, a negative correlation was observed. Therefore, larger, more diluted droplets were required to get the best trifloxysulfuron effectiveness.